2015
DOI: 10.3390/e17117608
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Scale Entropy Analysis of Body Sway for Investigating Balance Ability During Exergame Play Under Different Parameter Settings

Abstract: Abstract:The goal of this study was to investigate the parameters affecting exergame performance using multi-scale entropy analysis, with the aim of informing the design of exergames for personalized balance training. Test subjects' center of pressure (COP) displacement data were recorded during exergame play to examine their balance ability at varying difficulty levels of a balance-based exergame; the results of a multi-scale entropy-based analysis were then compared to traditional COP indicators. For games i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…As shown in Table 5, we found by categorizing fallers and non-fallers by critical values from clinical tests using MSE. MSE has previously been used to detect the complexity of physiological signals, such as heart beat [30,51,52] brain waves [53], acceleration [32], and postural stability [52,54]. The results all showed that MSE can effectively identify objective data.…”
Section: Resultsmentioning
confidence: 96%
“…As shown in Table 5, we found by categorizing fallers and non-fallers by critical values from clinical tests using MSE. MSE has previously been used to detect the complexity of physiological signals, such as heart beat [30,51,52] brain waves [53], acceleration [32], and postural stability [52,54]. The results all showed that MSE can effectively identify objective data.…”
Section: Resultsmentioning
confidence: 96%
“…Our study is different from previous studies, in that previous studies have used MSE to determine the physiological and pathological events of aging [ 11 , 12 , 18 21 , 51 , 52 ], whereas we used MSE to determine the equipment that measures the performance of postural stability. We attempted to generalize the applications of complexity index to tasks [ 53 ] and training characteristics and to explore different tools to obtain different results.…”
Section: Discussionmentioning
confidence: 99%
“…Even though both use all features or only important features, eye-movement complexity features are consistently superior in detecting computer activities. The basic nature of complexity-based features that are containing “implicit” information about body responses to the human activity and states [ 46 , 47 ] has benefited AI models to help them to overcome the prediction confusedness (compare Table 4 with Table 5 ). As was expected, the findings in this study prove that complexity analysis is also suitable for eye-movement-based data, as useful as its usage in human heart rate [ 16 ], cerebral hemodynamics [ 17 ], blood pressure [ 18 ], and body movements [ 19 , 48 ] data.…”
Section: Discussionmentioning
confidence: 99%